(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article is devoted studying of main theoretical aspects of international tourism as a form of international economic affairs. Features of the functions – social, economic and humanitarian - are described. There are also mentioned the main principles and features on which the international tourism is based. Analyzed the terms interpretation of the modern international market of tourist service.